Synthesis and CuII coordination chemistry of a patellamide derivative: consequences of the change from the natural Thiazole/Oxazoline to the artificial imidazole heterocycles - Comba, Peter; Dovalil, Nina; Hanson, Graeme R.; Linti, Gerald W. (Inorganic chemistry, 2011)
The synthesis and CuII coordination chemistry of the cyclic pseudo-octapeptide H4pat1, a dimethyl-imidazole analogue of naturally occurring cyclic peptides (patellamide A-F, ascidiacyclamide) is reported. Substitution of the oxazoline and thiazole heterocycles by dimethyl-imidazoles leads to a slightly different structure of the macrocycle in the solid state. The CuII coordination chemistry of H4pat1, monitored with high-resolution electrospray mass spectrometry, spectrophotometric titrations, and EPR spectroscopy, revealed the presence of both mono- and dinuclear CuII complexes. The dimethyl-imidazole analogue shows a high cooperativity in CuII coordination, that is, the preferred formation of dinuclear complexes. The dinuclear unbridged CuII complexes of H4pat1 have unusual EPR features, reminiscent of those of patellamide D: the dipole-dipole interaction of the CuII centers is negligible due to the “magic angle” orientation of the two CuII ions. Density functional theory calculations (DFT) are used to model the structures of the CuII complexes, and the structural assignments from the spectroscopic investigations are supported by the optimized and by X-ray structures of the metal-free macrocycle and dinuclear CuII complexes of H4pat1. The rigidity of the dimethyl-imidazole rings has a significant effect on the structures of the metal-free ligands and CuII complexes and therefore changes the properties of these compounds. This may explain why Nature has chosen the thiazole-oxazoline combination for the patellamides and ascidiacyclamide.